Penerapan Metode Diskusi Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran IPAS Kelas IV SD Negeri 1 Towangsan - Cahya Hidayati; Nela Rofisian; Isna Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to increase students' learning motivation using the discussion method in class IV science and science subjects at SD Negeri 1 Towangsan. This research is Classroom Action Research (PTK). The subjects of this research were 16 grade IV students at Towangsan State Elementary School. The object of this research is the application of discussion methods and student learning motivation. The data collection techniques used are observation, questionnaires and documentation. The data obtained were in the form of questionnaire results, observation results and documentation results as primary data, as well as learning results tests as supporting data. The data analysis techniques used are quantitative and qualitative descriptive. The results of this research indicate that the application of the discussion method in science and science learning can increase the learning motivation of class IV students at SD Negeri 1 Towangsan. This is proven by the average science learning motivation of students increasing from cycle I by 67.43% to 75.31% in cycle II and is in the good category. In line with this, the average learning evaluation results increased, namely from cycle I it was 65.00% in the medium category, increasing to 78.12% in the good category. From the results of this research, it can be concluded that the Discussion Method applied in science and science learning is effective in increasing the learning motivation of class IV students at SD Negeri 1 Towangsan.